The Alkylation and Reduction of Heteroarenes with Alcohols Using Photoredox Catalyzed Hydrogen Atom Transfer via Chlorine Atom Generation. Issue 10 (18th July 2019) - Zidan, Montserrat; Morris, Avery O.; McCallum, Terry; Barriault, Louis
Abstract : Radical additions to heteroaromatic bases are frequently employed for the rapid synthesis of complex products using C–H functionalization strategies. The conditions that are commonly employed are typically harsh, routinely requiring stoichiometric oxidants and other additives. In search for milder reaction environments allowing late‐stage functionalization, we present the alkylation of N‐heteroarenes using primary alcohols and ethers as radical precursors, where the corresponding alkyl radical is formed via hydrogen atom transfer process with a photoredox catalyzed chlorine atom generation as HAT agent. Furthermore, we explore the reduction of the heteroarenes in moderate to high yields when using secondary alcohols. Abstract : The alkylation of N‐heteroarenes using primary alcohols and ethers as radical precursors. The corresponding alkyl radical is formed via hydrogen atom transfer (HAT) process with a photoredox catalyzed chlorine atom generation as HAT agent. Furthermore, we explore the reduction of the heteroarenes when secondary alcohols are employed, giving moderate to high yields.